New Insights into In Vivo Human Skeletal Muscle Function - Kawakami, Y.; Fukunaga, T. (Exercise and Sport Sciences Reviews, 2006)
Approaches to understanding human muscle function through measuring in vivo muscle fiber behavior in humans are described briefly. Experimental results show the discrepancy between joint actions and muscle fiber behavior in many occasions, which complicates prediction of muscle mechanics from sole observations of joint actions. This is the result of muscle-tendon interaction during contraction, which is efficiently used during human movements.